Epinephrine: Systemic Effects and Varying Concentrations in Local Anesthesia - Cassidy, James P. (1986)
The range of vasoconstrictors available for use with local anesthetics in dentistry has been reviewed with emphasis on epinephrine and its physiological effects. All of the vasoconstrictors reviewed provide satisfactory results in dental anesthetic solutions when administered in appropriate concentrations and volumes. Possible drug interactions of concern to dentists include the use of vasoconstrictors with inhalational anesthetics, tricyclic antidepressants, beta blockers and, possibly, phenothiazines. Data reviewed indicates that the amounts of epinephrine used in dentistry can result in significant elevations in circulating levels of ephinephrine and concomitant physiologic changes. Evidence reviewed suggests that 1:200,000 epinephrine concentration results in optional duration and depth of local anesthesia. With the potential for adverse effects from epinephrine concentrations that are needlessly increased, it appears that in most clinical situations a 1:200,000 concentration of epinephrine can be used in an efficacious manner.